(untitled) (Fiep Bulletin - online, 2013)
Anxiety is a normal reaction to any individual, but is now recognized as pathological when it becomes excessive, leading to a decrease in quality of life, loss of performance and emotional distress. The Generalized Anxiety Disorder (GAD) affects 5.1% of the population, with a prevalence of 11.5% of the care in public health facilities. Objective: To assess the improvement of symptoms in patients with GAD anxiolytics by auricular acupuncture. Methodology: This was a quasi-experimental study, quantitative. The study included 60 subjects of both sexes aged between 20 and 64 years suffering from GAD. To review the TAG were used two questionnaires, scales Hamilton and Zung, applied before and after the intervention. 10 applications were made of auricular acupuncture points Shen Men, sympathetic, Rim, Stress, Anxiety and Stomach 1 and 2 with 1.5 mm needles. The volunteers were randomly divided into two groups of 30, one treated and one control group. Results: The study showed a 68% improvement in symptoms of GAD according to the Hamilton scale and between 90 and 95% improvement in Zung Scale. Conclusion: The results obtained in this study it was concluded that the use of auricular acupuncture was effective for GAD, suggesting the possibility of its use in public and private segments as an effective strategy and low cost.